Surveying for engineers - Uren, John (Macmillan, 1994)
This classic text takes the reader through everything they need to know, from traditional methods through to the very latest technological developments. Ideal whether students are studying surveying as a separate discipline or as part of a civil engineering, building or construction course: accessible, well illustrated and comprehensive.